Combination of Salinomycin and AZD3463 Reveals Synergistic Effect on Reducing the Viability of T98G Glioblastoma Cells - Asik, Aycan; Ay, Neslihan P.O.; Bagca, Bakiye G.; Caglar, Hasan O.; Gunduz, Cumhur; Avci, Cigir B. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Salinomycin, an ionophore antibiotic, is known to be an effective agent in reducing the viability of Glioblastoma (GBM) cells. The combination of salinomycin with other chemotherapeutic drugs would help to overcome the drug resistance of GBM cells. Objective: This study aims to test the combinatorial effect of salinomycin and AZD3463 in T98G GBM cells. Methods: The cytotoxic effects of drugs on T98G GBM cells were determined by using WST-8 assay. Flow cytometry was used to identify apoptosis and cell cycle profiles after treatments. Real-time PCR was used to portray mRNA expression profiles of genes in the Wnt-signaling pathway after treatments. Results: IC50 concentrations of AZD3463 and salinomycin were 529nM and 7.3μM for 48h, respectively. The combination concentrations of AZD3463 and salinomycin were 3.3μM and 333nM, respectively. The combination treatment showed a synergistic effect on reducing the viability of GBM cells. AZD3463, salinomycin, and their combination induced apoptosis in 1.2, 1.4, and 3.2 folds, respectively. AZD3463 and the combination treatment induced the cell cycle arrest at the G1 phase. Salinomycin and AZD3463 treatments, either alone or in combination, resulted in the downregulation or upregulation of mRNA expression levels of genes in the Wntsignaling pathway. Conclusion: Salinomycin, AZD3463, and their combination may inhibit proliferation and induce apoptosis in GBM cells due to a decrease in expression levels of genes acting in both the canonical and non-canonical Wnt signaling pathways. The Wnt signaling pathway may be involved in salinomycin-AZD3463 drug interaction.
Keywords: Anaplastic lymphoma kinase